Synthesis of mesoporous composite file (polyaniline-copper(I) oxide) from lyotropic liquid crystalline template. - Zhong, Da Hua. (2010)
Mesoporous semiconductor film created through electrodeposition from lyotropic liquid crystal (LLC) template are of great interest as they have great surface area-to volume ratio and have potential applications in solar cells and catalysis usage etc. In this project, a mesoporous composite film was created, with the idea that the use of mesoporous Polyaniline film as support for the deposition of mesoporous Copper (I) Oxide will be able to enhance the surface area and semiconductor properties of Copper (I) Oxide.